Surgery for aortic stenosis in severely symptomatic patients older than 80 years: experience in a single UK centre. Issue 2 (1st August 1999) - Gilbert, T; Orr, W; Banning, A P
Abstract : OBJECTIVE: To ascertain the surgical risk and long term outcome of patients over 80 years old undergoing aortic valve replacement (AVR). DESIGN: Consecutive cases with respective case note audit and a telephone questionnaire. SETTING: Single UK cardiothoracic surgical centre. PATIENTS: 103 (48 male) patients over 80 years old undergoing AVR. The median age was 82 years (80–95 years) and 95 of 103 patients were in New York Heart Association (NYHA) class III or IV. METHOD AND RESULTS: Preoperative characteristics, operative course, cost, and outcome measures were ascertained. Mean bypass time was 56 minutes and 25 patients had simultaneous coronary artery bypass grafting. Overall mortality was 19 of 103. Univariate analysis of pertinent variables found that impaired renal function and peripheral vascular disease were significantly associated with early postoperative death. 10 of 12 patients requiring ventilation for more than 24 hours died. The 50% actuarial survival was 62 months. Late complications were uncommon with 92% of patients in NYHA class I or II at follow up. CONCLUSIONS: AVR in patients over 80 years old has a significant risk. However, those patients who survive experience significant benefit with good long term prospects for general health and social independence.